Surrogate Experiential Learning-Based Science Subject Specific Pedagogy (SSP) to Build Disaster Preparedness of Junior High School Students on Volcanic Eruption - Widodo Setiyo Wibowo; Sabar Nurohman; Allesius Maryanto (Journal of Science Education Research, 2018)
The study was conducted to develop surrogate experiential learning (SEL)-based science Subject Specific Pedagogy (SSP) that is feasible to be implemented in science learning and potentially to build volcanic eruption disaster preparedness of junior high school students. The study was Research and Development (R and D), modified from Borg and Gall steps covering only research and information collecting, planning, preliminary form of product development, expert judgment, product revision, and final product. The subjects were 2 expert lecturers (content expert and media expert) and 2 science teachers of SMP N 2 Cangkringan. The types of data were quantitative and qualitative. Data were collected by means of SSP validation sheets and disaster preparedness identification sheets. The techniques of data analysis were descriptive analysis of qualitative and quantitative to 5 grading scale. The result of the study shows that SEL-based science SSP is feasible to be implemented in science learning and potential to build volcanic eruption disaster preparedness of junior high school students.